Optimasi Balok Kastela Berdasarkan Atas Perbandingan Jarak Perlubangan - Ngudi Hari Crista; Bambang Purnijanto; Mukti Wiwoho (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2015)
Kastela beam is a steel beam with the body open vertical height is doubled because the preparation of the half-pieces of the agency. Optimization of structures with variable geometry design is called a hole shape optimization, therefore, the re-calculation is required for each change of shape, so it takes a long computation time. The study aims to get the shape, size and spacing holes hexagonal shape and the distance between the holes with the same height of the perforation, in order to get the configuration or layout optimal pit, and knowing that occurs between the beam deflection Kastella with its original profile. Computerized simulation method used by SAP 2000 version 14 to 5 samples to obtain the optimum size hole distance on the I profile steel beams with hexagonal openings and the loading condition that a distributed load along the span and the load point at midspan. The simulation results show that the ratio of the smallest voltage occurs in the second sample, ie Kastella beam with a distance of 15 cm with perforations voltage value 1723.49 kg / cm2, while the ratio of the greatest stress on the sample IV Kastella beam with a distance of 25 cm with perforations voltage value 1968.21 kg / cm2. The smallest deflection occurs in sample II with a perforation spacing of 15 cm with a value of 0.2083 mm, while for the greatest deformation occurs in the sample IV with perforation spacing of 25 cm with a value of 0.2811 mm deformation, so the distance, shape, and it is best pelubangannya perforations with a distance of 15 cm for configuration or layout optimal pit. Further analysis of the cellular hole shape optimization, either circular or elliptical shape and layout of the hole, taking into account the instability I profile steel beams with cellular openings in body shape, due to bending and buckling in the web-post area.